LAWS: ferramenta web para anotações manuais em arquivos audiovisuais - ESTUMANO, Jeremias Kalebe Cunha (2022)
Linguists spend hours annotating audiovisual media. And the ease of access and handling of the tools is very important in the performance of their work. There is the ELAN tool, which is widely used today, for annotations. However, its robust interface and high degree of complexity makes it a challenge for beginners. Thus, a new tool was needed, which is web, simple and with an easy-to-view interface. We present Laws, a web tool, to facilitate access, handling and documentation in linguistics. LAWS can be accessed from this link: https://marcosamaris.github.io/laws/.